Metafora dalam lirik lagu Berita Pada Kawan ciptaan Ebiet G. Ade: Kajian semantik - Gusvita, Widya; Dita Rizqi Mawaddatur Rohmah; Rifa’atussalwa Hayati (Universitas Tangerang Raya, 2023)
This study aims to describe the use of metaphors and find out some of the metaphors in the lyrics of the song Berita Untuk Kawan created by Ebiet G. Ade for learning Indonesian Semantics. The type of research used is qualitative based on descriptive methods which are carried out when researchers want to know answers to problems with a phenomenon that is happening. The data used in this study are metaphors that are obtained or found in every word or in every phrase with certain data collection steps. The results of this study are that there are 8 metaphors in the lyrics of the song Berita Untuk Kawan created by Ebit G. Ade consisting of: rocky dry land, street stones, little shepherds, sea, coral, waves, sun, and grass. The metaphors obtained from the song contain many meanings related to something that is felt and encountered by someone in solitude while traveling. By knowing some of the metaphors in the lyrics of the song Berita Untuk Kawan, created by Ebiet G.Ade. then we can understand the thoughts, meanings, and messages expressed, so that we can enrich the vocabulary that is suitable for learning Indonesian Semantics.